Conservation of Built Heritage in India Heritage Mapping and Spatializing Values - J., Vijayalaxmi (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book focuses on the Heritage Conservation of Architecture, Historic Districts of a City and Conservation strategies with specific case studies from India, in order to highlight the need for conserving the rich piece of history through research, education, advocacy, and practice. The historic significance and the condition mapping of the subjects are carried out through primary field studies by the authors at School of Planning and Architecture, Vijayawada, India. The cases are analysed, and appropriate solutions and sustainable strategies are evolved for the conservation of the buildings facing contemporary challenges. The contents align with the Sustainable Development Goals (SDG 11), Target 11.4 which aims to "strengthen efforts to protect and safeguard the world's cultural and natural heritage'. This would ensure that a rich piece of history is documented and analysed to ensure that it is not erased and forgotten. This book serves as a bountiful data base of literature as well as conservation strategies for heritage conservationists, students of architectural conservation and researchers.
Conservation of Heritage in India- Challenges, Issues, Agencies and Technological advancements -- Heritage significance of the historic town of Padmanabhapuram, India and its tourism potential -- The Lost heritage of Bengaluru City - the case of Chikkajala fort -- Study of the Planning and Architectural Significance of the Chitnavis Wada in Nagpur, India -- A study on Defense Planning Strategies of Gwalior fort -- Holistic study to comprehend influence of Orissa and West Bengal on Temple styles in Nagpur -- Human perception analysis of adapting vernacular architectural solutions in urban single residences -- Public Perception of the Significance of Cultural Heritage Conservation for Promoting Community Wellbeing -- Evaluating the Adaptive Reuse Potential of Chettinad Houses for Heritage Conservation -- Holistic Study and Analysis of Adaptive Reuse of Historic Structure. .
Keywords: Sustainability; Cultural property; Buildings -- Design and construction; Architecture; Buildings; Sustainability; Cultural Heritage; Building Construction and Design; Building Types and Functions